2010
DOI: 10.1007/s11242-010-9554-3
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Alteration of Porous Media Wettability from Liquid-Wetting to Intermediate Gas-Wetting

Abstract: Wettability of Berea and low permeability reservoir rocks are permanently altered from liquid-wetting to intermediate gas-wetting. We use water and decane as model liquid, and air and nitrogen as model gas in the experiments. New chemicals with various functional groups are used in the wettability alteration. We perform compositional analyses of the treated chemical solutions extracted from rock treatment by gas chromatography-mass spectrometry (GCMS) and by inductively coupled plasma-mass spectrometry (ICPMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 38 publications
(39 reference statements)
2
60
0
Order By: Relevance
“…Noh and Firoozabadi (2008) used an alcohol-based surfactant polymer solution to study the wettability alteration to intermediate gas wetting, with experimental results showing a considerable increase in water mobility. More recently, Wu and Firoozabadi (2010) demonstrated the permanency of the wettability alteration by providing a chemical reaction between rock and new chemicals having various functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Noh and Firoozabadi (2008) used an alcohol-based surfactant polymer solution to study the wettability alteration to intermediate gas wetting, with experimental results showing a considerable increase in water mobility. More recently, Wu and Firoozabadi (2010) demonstrated the permanency of the wettability alteration by providing a chemical reaction between rock and new chemicals having various functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…The contact angle of water on the rocks treated with these three reference nanofluids was obtained ˃160 ° while 150 ° is the best result for water contact angle on the rock reported until now [5,6]. It is worth noting that the reference nanofluids also could interestingly create coatings with self-cleaning property on the rock samples which fluoro-polymers/surfactants [2][3][4][5][6][7][8][9][10][11][12][13][14] and fluorinated nanosilica solutions [35] were not able to do.…”
Section: Tablementioning
confidence: 99%
“…Many researchers have made contributions toward using various fluorinated polymers or surfactants to change the wetting nature of a series of chalk and sandstone rocks [2][3][4][5][6][7]. As a result, they demonstrated that wettability alteration had substantial effect on improving liquid mobility and gas productivity of treated rocks.…”
Section: Introductionmentioning
confidence: 99%
“…The wettability alteration as a result of the adsorption of the treatment chemicals onto the core surface is believed to have only a small effect on the reduction of the absolute permeability of a core sample. However, some chemicals cause a reduction in the absolute permeability of a porous medium when the permeability of core samples is less than 1 Darcy (Fahes and Firoozabadi 2007;Noh and Firoozabadi 2008;Wu and Firoozabadi 2010). Silane compounds with a low molecular weight have negligible effect on the absolute permeability reduction of a core sample during the wettability alteration process (Wu and Firoozabadi 2010).…”
Section: Oil Production Historymentioning
confidence: 99%
“…However, some chemicals cause a reduction in the absolute permeability of a porous medium when the permeability of core samples is less than 1 Darcy (Fahes and Firoozabadi 2007;Noh and Firoozabadi 2008;Wu and Firoozabadi 2010). Silane compounds with a low molecular weight have negligible effect on the absolute permeability reduction of a core sample during the wettability alteration process (Wu and Firoozabadi 2010). The increase in the live oil production rate with the oil-wet beads composition is expected to be a result of better wetting conditions in the oil-wet regions.…”
Section: Oil Production Historymentioning
confidence: 99%